IMPLEMENTASI KEBIJAKAN PANGAN SEHAT DAN BEBAS BAHAN BERBAHAYA DI KOTA PAYAKUMBUH - Rifandra Akbari; Hasim As’ari (Cross-border, 2022)
Before starting a business, business actors such as the Home Food Industry (HFI) must have dealt with administrative matters such as permits. The Payakumbuh City Government has also regulated this in the Payakumbuh City Regional Regulation Number 1 of 2014 concerning Healthy Food and Free of Hazardous Materials, it is stated "The Regional Government/Mayor through the Health Office issues certificates of food safety, quality and nutrition". However, the field shows that there are still many who do not have food safety, quality and nutrition certificates such as Home Industry Food Production Certificate. This study aims to analyze the Implementation of Healthy Food Policy and Free of Hazardous Materials for the Home Food Industry in Payakumbuh City, especially in obtaining food safety, quality and nutrition certificates. This study uses a descriptive qualitative method with data collection techniques in the form of interviews, observations and documentation. The results of this study are the implementation of the policy of Healthy Food and Free of Hazardous Materials, especially in the implementation of certificate management, quality safety, and nutrition such as SPPIRT in Payakumbuh city is not optimal, because there are still many Home Food Industries that do not yet have and important matters related to distribution license number for business.